2018
DOI: 10.1002/jor.24164
|View full text |Cite
|
Sign up to set email alerts
|

VEGF with AMD3100 endogenously mobilizes mesenchymal stem cells and improves fracture healing

Abstract: A significant number of fractures develop non‐union. Mesenchymal stem cell (MSC) therapy may be beneficial, however, this requires cell acquisition, culture and delivery. Endogenous mobilization of stem cells offers a non‐invasive alternative. The hypothesis was administration of VEGF and the CXCR4 antagonist AMD3100 would increase the circulating pool of available MSCs and improve fracture healing. Ex‐breeder female wistar rats received VEGF followed by AMD3100, or sham PBS. Blood prepared for culture and col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 44 publications
0
19
0
2
Order By: Relevance
“…They stabilized with an external fixator a 1.5mm femoral osteotomy in rats. The bone volume was increased in animals treated with VEGF and AMD3100 30 .…”
Section: Resultsmentioning
confidence: 97%
“…They stabilized with an external fixator a 1.5mm femoral osteotomy in rats. The bone volume was increased in animals treated with VEGF and AMD3100 30 .…”
Section: Resultsmentioning
confidence: 97%
“…Strategies to enhance healing by mimicking the natural cellular processes that occur during skeletal development are actively being explored. Most notably, transplantation of tissue specific progenitor cells or stimulating the recruitment of endogenous/native progenitors are approaches that are utilized to enhance healing of skeletal tissues in preclinical models [15][16][17][18][19]. The self-renewal capacities of skeletal tissues diminish with aging.…”
Section: Common Progenitor/stem Cells Utilized For Skeletal Tissue Rementioning
confidence: 99%
“…It was widely demonstrated that bone metastatic cancer cells displayed a characteristic pattern of homing in the long bones, with the majority of tumor cells seeded in the trabecular regions. In addition, it was showed that the mobilization of Human Stromal Cells (HSCs) from the niche resulted in increased numbers of tumour cells disseminated in trabecular regions [64]. It has been also demonstrated that the administration of the CXCR4 antagonist AMD3100 seems to increase the circulating pool of mesenchymal stromal cells (MSCs) improving the fracture healing [65] In addition it was also demonstrated that CXCR4 sustain osteogenic differentiation [66].…”
Section: Effects Of Cxcr4 and E-selectin Antagonism On Osteoblast Andmentioning
confidence: 99%